DARI TEORI KE PRAKSIS: TRANSFORMASI PEMAHAMAN GOVERNANCE NETWORK MELALUI DIALOG INTERAKTIF MAHASISWA UIN ALAUDDIN MAKASSAR - Rukmana, Novayanti Sopia; Syam, Febrianto; Manda, Darman; Johansyah, Oky Nur Pratiwi; Fitri, Anisa (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2025)
Food security is a strategic issue that requires a governance network approach through multi-stakeholder collaboration. However, students at UIN Alauddin Makassar have a limited understanding of the concept of governance networks and their application in food security policies. This community service activity aims to improve students' understanding of governance networks through book reviews and interactive dialogues. The method used is a participatory approach with experiential learning conducted in three stages: preparation, implementation, and evaluation. The activity was held on November 20, 2024, at UIN Alauddin Makassar, involving 50 students from various study programs. The speakers consisted of practitioners from WIKIPangan Sulawesi Selatan and political science lecturers who provided theoretical and practical perspectives. The evaluation employed a mixed-methods approach comprising pre-and post-tests, Focus Group Discussions, and in-depth interviews. The results showed a 41.6% increase in understanding (from a score of 58.4 to 82.7), with 88% of participants achieving a score above 70. There was a 34.2% increase in positive attitudes toward multi-stakeholder collaboration, and 76% of participants expressed interest in actively participating in governance and public policy activities. The activity successfully transformed students' understanding from a theoretical to a practical level and fostered change agents capable of applying governance networks to address food security issues. The long-term impact is the emergence of a generation of leaders who understand the importance of collaboration in public policy.